How Islamic Lifestyle Affects Housewives' Responses to Product Availability, Service Quality, and Promotions in the Use of the Alfagift Application in Parepare City - Reski Mahmud; Arwin; Umaima; Multazam Mansyur Addury (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of product availability, service quality, and promotion on the purchasing decisions of Alfagift app users in Parepare City with Islamic lifestyle as a moderating variable. The study uses a quantitative approach with a survey method on 125 housewives selected through purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS. The outer model test results showed that all indicators met the validity and reliability criteria with factor loading values > 0.70, AVE > 0.50, and Composite Reliability > 0.70. The inner model test produced an R² value of 0.780, indicating the model's strong explanatory power. The hypothesis test results prove that product availability (β = 0.515), service quality (β = 0.383), and promotion (β = 0.445) have a positive and significant effect on purchasing decisions. In addition, Islamic lifestyle has a significant effect and is able to positively moderate the influence of these three variables on purchasing decisions, thereby strengthening the role of religious values in digital consumption behavior.